Excellent Vocational School Development Management in Indonesia - Satibi, Imam (Lembaga Bale Literasi, 2023)
This study aims to analyze the formulation/planning, implementation, evaluation, barriers, and solutions to strategies for improving the quality of Vocational High Schools in Kebumen. This research is qualitative research with the subject of research is Vocational High School which has an excellent predicate in Kebumen Regency, which is 3 schools are SMK N 1 Gombong, SMKN 2 Kebumen dan SMK Ma’arif 1 Kebumen. Data collection techniques in the form of questionnaires, interviews, and documentation. The data analysis technique uses your Miles Huberman model. The results of the analysis show that the strategic management of superior vocational school includes planning, implementation, and evaluation. Planning includes environmental analysis, SWOT analysis, formulation of goals such as making a global standard vision and mission. Implementation refers to three things, namely development, establishment, growing up. While the evaluation uses a monitoring technique with the POAC stage. Some of the obstacles faced in developing superior vocational schools are the limited skills possessed by human resources, lack of link and match with the international community, lack of language skills, and so on.